ANALISIS KORELASI DAN REGRESI ANTARA UKURAN-UKURAN TUBUH DENGAN BOBOT BADAN SAPI BRAHMAN CROSS (BX) BETINA DI KPT MAJU SEJAHTERA DESA TRIMULYO, KECAMATAN TANJUNG BINTANG, KABUPATEN LAMPUNG SELATAN - Obet Yanto; Muhammad Dima Iqbal Hamdani; Dian Kurniawati; Sulastri Sulastri (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2021)
This study aimed to determine the Correlation and the regression equation between body measurements and body weight of Brahman Cross (BX) Cow in KPT Maju Sejahtera Trimulyo village, Tanjung Bintang District, Lampung Selatan Regency. This research was conducted in July 2020. The data obtained were analyzed using simple and multiple regression analysis using the help of the Excel program. The material used in this study were 32 Brahman Cross (BX) Cow aged 2-3 years. The results of this study indicated that the average of Body Weight (BW), Chest Circumference (CC), Body Length (BL), and Shoulder height (SH) were 472.66 ± 53.59 kg, 179.95 ± 7, 95 cm, 132.49 ± 6.39 cm, 127.95 ± 3.08 cm, respectively. The correlation value between CC, BL, SH with BB were 0.764, 0.448, and 0.551, respectively. These results indicated that CC, BL, SH, have a positive relationship with BW. The regression equation resulting from the relationship between body weight and body size CC, BL, SH to BW with the value of determination (R2) and significance (P˂0.05) was 0.607 (60.7%) with the regression equation BW = -674.003 + 4.314 CC + 1.247 BL + 1.602 SH. Keywords: Brahman Cross, Body Measurement, Correlation and Regression